Treatment and Nursing Values of Cd(II) Complex with Photocatalytic Activity on Bacterial Infection by Inhibiting the Gram-Positive Bacteria Growth - Jing Peng; Quan-Zhen Tang; Jian Lu; Yan Hu; Jiao Ni (International Journal of Polymer Science)
Presented here is a trinuclear cluster-based Cd(II) compound, namely, {[(CH3)2NH2][Cd6K(bdc)6(btz)3(H2O)6]}n (1 H2bdc = terephthalic acid, Hbtz = 1H-benzotriazole), has been solvothermally prepared and structurally determined by the single crystal X-ray diffraction analysis, elemental analysis, powder X-ray diffraction analysis, and thermogravimetric analysis. Notably, compound 1 shows excellent photocatalytic activity for degradation of MV irradiated by UV light. In addition to this, the biological activity of the new compound on bacterial infection was evaluated, and the corresponding mechanism was also studied. The ELISA assay was used to evaluate the TNF-α and IL-1β released into plasma after compound treatment. Then, the relative expression levels of the bacterial survival gene were measured with real-time RT-PCR.